Chemical and sensory differences between high price and low price extra virgin olive oils. (March 2018) - Fiorini, Dennis; Boarelli, Maria Chiara; Conti, Paolo; Alfei, Barbara; Caprioli, Giovanni; Ricciutelli, Massimo; Sagratini, Gianni; Fedeli, Donatella; Gabbianelli, Rosita; Pacetti, Deborah
Abstract: The aim of the study was to identify new potential chemical markers of extra virgin olive oil (EVOO) quality by using a multicomponent analysis approach. Sixty-six EVOOs were purchased from the Italian market and classified according to their price as low price EVOOs (LEVOOs) and high price EVOOs (HEVOOs) costing 3.60–5.90 euro/L and 7.49–29.80 euro/L respectively. Sensory and chemical parameters strictly related to olive oil quality have been investigated, like volatile substances, polar phenolic substances, antioxidant activity, fatty acid composition, and α-tocopherol. Significant differences in terms of chemical composition and sensory features have been highlighted between the two EVOOs classes investigated, proving a generally lower level of quality of LEVOOs, clearly showed also by means of principal component analysis. Among the most interesting outcomes, R ratio (free tyrosol and hydroxytyrosol over total free and bound forms), measuring the extent of secoiridoids hydrolysis, resulted to be significantly higher in LEVOOs than in HEVOOs. Other key differences were found in the volatile substances composition, in the stearic acid percentage and in p -coumaric acid content. Graphical abstract: Highlights: Multicomponent study on low (LEVOO) and high price extra virgin olive oils (HEVOO) Significantly higher sensory quality in HEVOOs than in LEVOOs R ratio (indicating hydrolysis extent of secoiridoids) significantly higher in LEVOO than in HEVOO Ratio hexanal/2-( E )-hexenal significantly higher in LEVOO than in HEVOO Stearic acid % and p -coumaric acid content significantly higher in LEVOO than in HEVOO